Implementation of The Sales and Purchase Program Application Using The Rapid Application Development Model Web – Based - Ichsan, Aulia; Al-Khowarizmi, Al-Khowarizmi; Azhari, Mulkan (Tsabit Journal of Computer Science, 2024)
The development of information technology is currently developing rapidly and rapidly, which is supported by one of the means, namely computers. Of course, computers that are equipped with certain applications are used to help make human work easier in managing data for an organization or company so that they get accurate results that meet their needs. The results of observations that have been made show that sales and purchasing activities still use manual systems, one of which is in clothing stores. Starting from processing goods data, difficulties checking stock, purchasing transactions, sales transactions, as well as storing other data related to all types of activities, which can cause losses for shop owners, errors in recording and inaccurate reports being made. Judging from the large number of transactions carried out at clothing stores, a faster and more accurate information system is needed. Therefore, the author created a computerized program design using the Microsoft Visual Basic.net programming language and MySQL database, so that information and activities that occur can be carried out quickly and accurately. The method used in designing this program uses the Rapid Application Development (RAD) model. This RAD model is an adaptation of the high-speed version of the waterfall model for the development of each software component. The results achieved from discussing this theme are in the form of ready-to-use sales and purchasing program applications. In this case, the use of program applications is the best solution to solve existing problems, and by using program applications an effective and efficient activity can be achieved in supporting activities, especially for handling sales and purchasing problems.